The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2188/jea.je20080043
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and All-cause Mortality in Japan: The Jichi Medical School (JMS) Cohort Study

Abstract: BackgroundIn April 2008, a new health check-up and health guidance system was introduced by the Japanese Government to promote increased physical activity. However, few studies have documented the health benefits of physical activity in Asian populations. We examined the association between all-cause mortality and level of physical activity in a Japanese multicommunity population-based study.MethodsThe Jichi Medical School Cohort Study is a multicommunity, population-based study based in 12 districts in Japan.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 15 publications
1
33
0
2
Order By: Relevance
“…Many studies have examined the association between physical activity and all-cause death 811 and reported an inverse dose–response relationship between them 8 ; however, some studies have shown a reverse J-shaped, 9 L-shaped, 10 J-shaped, or U-shaped 11 curve. We found that physical activity was associated with a slight inverse dose–response relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have examined the association between physical activity and all-cause death 811 and reported an inverse dose–response relationship between them 8 ; however, some studies have shown a reverse J-shaped, 9 L-shaped, 10 J-shaped, or U-shaped 11 curve. We found that physical activity was associated with a slight inverse dose–response relationship.…”
Section: Discussionmentioning
confidence: 99%
“…5 , 6 Although some research indicates that only vigorous activity reduces the risk of chronic health conditions, 7 this is controversial. Studies have found a dose–response relationship, 8 as well as reverse J-shape, 9 L-shape, 10 J-shape, and U-shape 11 associations, between physical activity and all-cause death. Cancer is now the leading cause of death in South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…We reviewed 9 major prospective cohort studies of the role of physical activity or physical fitness at baseline in all-cause mortality and/or CVD outcomes in Japan ( Table 2) [42][43][44][45][46][47][48][49][50][51] . Total daily physical activity was assessed based on the estimated energy expenditure 52) , estimated walking time, the MET score (estimated by multiplying the intensity of physical activity by the duration of the activity) 53) , and/or the calculated physical activity index 54) .…”
Section: Major Prospective Cohort Studies In Japanmentioning
confidence: 99%
“…The design and methods have been reported previously. [18][19][20] Baseline data were obtained during mass screening examinations between April 1992 and July 1995, and were followed up until the end of 2005. A total of 12,490 individuals, including 754 individual CVD survivors, from 12 areas participated.…”
Section: Study Populationmentioning
confidence: 99%